Effectiveness of teacher-based nutrition interventions in addressing malnutrition among sub-Saharan children - Nsamba, Jonathan (International Journal of Health, 2021)
Introduction: To address the high malnutrition rates in Sub Saharan Africa, most programs addressing malnutrition have continuously been streamlined through the health system, yet this has not yielded results as expected. On the other hand, the education sector has shown an immense capacity to address some challenges, such as eliminating short-term hunger through School feeding programs. Yet, little attention has been given to teachers as far as implementing health and nutrition interventions. With an increased school enrolment rate in Sub Saharan Africa, teachers present huge potential as change agents.Objectives: To consolidate evidence about the effectiveness of teacher-based interventions in addressing malnutrition in Sub- Saharan Africa.Methods: A search strategy through online databases including EBSCO, PubMed, BASE, Cochrane, Google Scholar, LILACS, Project MUSE, TRIP Database, and Emerald Insight gave rise to 95,734 studies. These were identified and taken through a series of screening stages such that the most eligible were included to answer the review question.Results: Three studies fulfilled the inclusion criteria. Results showed that teacher-based interventions such as school lunch, deworming, vitamin A supplementation, and nutrition education positively affect the nutrition status of primary school children, school attendances, are sustainable and reach many children.Conclusion: There is a need to actively involve teachers in the primordial and primary prevention stages of malnutrition through strengthening nutrition education, supplementary programs and school gardening. Teachers have an essential role to play in the fight against Malnutrition in Sub Saharan Africa.Â Â